2018
DOI: 10.1159/000494129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Migration on Allergic Diseases

Abstract: Studies in migrant populations provide vital opportunities to investigate the role of environmental factors in the pathogenesis of allergic disorders. Differences in allergy prevalence have been observed between migrants and native-born subjects living in the same geographical location. Immigrants who migrate from less affluent countries with lower allergy prevalence tend to have a lower prevalence of allergic disorders compared to native-born residents of the more affluent host country. The patterns of allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 88 publications
1
17
0
Order By: Relevance
“…21,22 Immigration from a less developed/affluent country into a more developed/affluent country with higher AD prevalence rate was observed to correlate to a lower incidence of AD in migrants when compared to the native population. 23 In Australia, children born in Asia who subsequently migrated to Australia also had a lower risk of self-reported AD than their East Asian peers who were born in Australia. 24 Additionally, a study by…”
Section: Pre Valen Ce Of Atopic Dermatitismentioning
confidence: 96%
“…21,22 Immigration from a less developed/affluent country into a more developed/affluent country with higher AD prevalence rate was observed to correlate to a lower incidence of AD in migrants when compared to the native population. 23 In Australia, children born in Asia who subsequently migrated to Australia also had a lower risk of self-reported AD than their East Asian peers who were born in Australia. 24 Additionally, a study by…”
Section: Pre Valen Ce Of Atopic Dermatitismentioning
confidence: 96%
“…4,6 The risk factor of birthplace outside of Castellon was observed in the first survey, 19 and AD prevalence in the group age 6 ---7 years was lower than other zones; some studies found more AD prevalence in the migrant population than the native population considering the age of migration. 20 In general, females have higher AD incidence than males, although this is not consistent in all studies. 18,21 Other childhood AD risk factors were not related to AD incidence, including breastfeeding, pets, day care, siblings, and dog exposure in early life.…”
Section: Discussionmentioning
confidence: 78%
“…When discussing the concept of biodiversity and its impact on the regulation of the immune system throughout an individual life, there is no better model to study than that of the consequences of immigration and/or emigration, a phenomenon which has lead hundreds of thousands across the world to become exposed to a complete new indoor and outdoor environment. Immigration and emigration to industrialized areas and the adoption of a more Western lifestyle has quickly led to behavioral, environmental, and dietary changes as the process of migration exposes immigrants to changes in socioeconomic, cultural, psychological, and, notably, environmental factors (60). The prevalence of diseases can greatly vary in settings with different socioeconomic conditions but also between regions, countries, and centers within a city or country (61).…”
Section: Rural-industrial Gapmentioning
confidence: 99%